Fruticuline A, a chemically-defined diterpene, exerts antineoplastic effects in vitro and in vivo by multiple mechanisms - Corso, Claudia Rita; Stipp, Maria Carolina; Radulski, Débora Rasec; Mariott, Marihá; da Silva, Luisa Mota; de Souza Ramos, Edneia Amancio; Klassen, Giseli; Queiroz Telles, José Ederaldo; Oliveira, Cristhian Santos; Stefanello, Maria Élida Alves; Verhoeven, Arthur J.; Oude Elferink, Ronald P. J.; et al. (Scientific reports, 2020)
Natural products have been recognized as important bioactive compounds on the basis of their wide biological properties. Here we investigated the antitumor effect and molecular mechanisms of the diterpene Fruticuline A (fruti) from Salvia lachnostachys , in human cancer cell lineages and Solid Ehrlich Carcinoma in mice. Fruti reduced MCF-7 and HepG2 proliferation by the reduction of Cyclin D1 levels and decreased NF-κB gene levels in both cell types. Furthermore, fruti also induced apoptosis in HepG2 cells, reduced Bcl-2 gene expression and induced necroptosis by increasing Ripk in MCF-7 cells. In mice, fruti prevented tumor development and reduced Cyclin D1, Bcl-2 and Rela gene levels, and reduced the p-NF-κB/NF-κB ratio in tumor tissue. Furthermore, fruti induced necrosis and apoptosis, increased N -acetyl-β-D-glucosaminidase and TNF-α levels and reduced IL-10 and Vegf levels in tumor tissue. Collectively, fruti exerts antitumor effects through the inhibition of the NF-κB pathway, reducing Cyclin D1 and Bcl-2 levels. In vitro the apoptosis and necroptosis pathways are involved in the cellular death, whereas in vivo , cells undergo necrosis by increased tumor inflammation and reduction of angiogenesis. Thus, fruticuline A acts in tumor cells by multiple mechanisms and represents a promising molecule for drug development in cancer treatment.